Modified Simple Decompression of Ulnar Nerve in the Treatment of Cubital Tunnel Syndrome: Report of a Series of Cases - Balevi, M.; Ozturk, S. (Wolters Kluwer Medknow Publications, 2018)
Background/Aim: Ulnar compressive neuropathy is the second most common nerve compression in the upper extremity. Although numerous operative procedures have been defined for the treatment of cubital tunnel syndrome (CuTS), the best operative intervention remains controversial. The aim of this study is to discuss the efficacy of a modified simple decompression (MSD) of the ulnar nerve in the treatment of CuTS. Materials and Methods: Each patient was preoperatively examined, and the following data were recorded: initial complaint, duration of symptoms, and presence of Tinel's sign around the elbow, results of provocation by the elbow flexion test, and results of electrodiagnostic studies. Patients' preoperative clinical manifestations were determined based on Dellon's staging system and Bishop scores. Pre- and post-operative motor conduction velocity (MCV) of the ulnar nerve were also recorded. Under the regional anesthesia, 4 cm long curved skin incision, above and below the elbow, was made posterior to the medial epicondyle of the humerus and the ulnar nerve was seen. The nerve was released proximally as it passed through the medial intermuscular septum. The cubital tunnel retinaculum and flexor carpi ulnaris aponeurosis were then cut distally. Only the compressive fascial bands are released. Then, the cubital tunnel reticulum was sutured to subcutaneous tissue loosely to prevent subluxation of the ulnar nerve. Results: A total of 15 patients were operated. Postoperative electrophysiological study assessed at 3 months following surgery in 8 patients. In 7 of these patients (86%), the mean value of MCV had improved from 38.9 +/- 12.0 m/s to 48.1 +/- 11.9 m/s (P < 0.05). According to Bishop scoring system, 13 patients (86.7%) were clinically graded as excellent, 1 patient (6.7%) was graded as good, and only 1 patient (6.7%) was graded as fair. Conclusion: MSD is a technically simple, safe, and effective method without annoying complications.
Keywords: Anterior transposition; cubital tunnel syndrome; simple decompression; ulnar nerve